INFLUENCE OF HYDROGEN ADDITIVE TO FUEL, ON ECOLOGICAL INDICATORS AUTOMOBILE ICE - N. G. Pevnev; V. V. Ponamarchuk (Вестник СибАДИ, 2017)
The idea that use of hydrogen as the initiating additive to the main fuel, leads to increase in economic and ecological indicators of ICE is proved. Special attention is paid to physical and chemical properties of hydrogen and its role when burning in a combustion chamber. In article the example of theoretical calculation of parameters of a working body and calculation of quantity of separate components combustion materials is carried out. The calculation is for four-stroke petrol engine with multipoint injection and electronically controlled power supply system and ignition at different percentage ratios of gasoline and hydrogen. Results of calculations are analyzed.